2016
DOI: 10.1111/1541-4337.12230
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Extensive Feeding Systems on Growth Rate, Carcass Traits, and Meat Quality of Finishing Lambs

Abstract: This review aims to summarize the relevant published information about the effects of extensive feeding systems on the carcass and meat quality characteristics of lambs. Lambs finished in a feedlot or with supplementation under extensive systems exhibit faster growth rates, achieve target weights quicker, and produce heavier carcass weights when compared to grazing lambs. However, the literature also shows that finishing lambs on high-quality pasture can produce satisfactory growth rates without compromising c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 159 publications
(252 reference statements)
3
49
3
3
Order By: Relevance
“…The lambs that are usually reared under intensive farming and are fed concentrates and cereal straw until slaughter, within 90 days of age, produce meat with high n-6 concentrations (Brito, Ponnampalam, & Hopkins, 2016). The same authors cited that the PUFA of lamb meat are affected by the dietary concentrate ratio, and according to Mushi et al (2010), different dietary concentrate levels affect the fatty acid profile of the adipose tissue and increase the ratio of the desirable fatty acids (DFA) in the meat.…”
Section: Introductionmentioning
confidence: 99%
“…The lambs that are usually reared under intensive farming and are fed concentrates and cereal straw until slaughter, within 90 days of age, produce meat with high n-6 concentrations (Brito, Ponnampalam, & Hopkins, 2016). The same authors cited that the PUFA of lamb meat are affected by the dietary concentrate ratio, and according to Mushi et al (2010), different dietary concentrate levels affect the fatty acid profile of the adipose tissue and increase the ratio of the desirable fatty acids (DFA) in the meat.…”
Section: Introductionmentioning
confidence: 99%
“…219 There was no difference in muscle fat content among dietary treatments or finishing 220 periods (Table 1). Other authors have reported that lambs receiving concentrate diets 221 generally have higher growth rates (Fraser & Rowarth, 1996) and IMF than lambs receiving 222 pasture-based diets (De Brito et al, 2017). However, Crouse et al (1978) found no difference 223 in fat thickness or percentage carcass fat of lambs fed low, medium or high energy diets and 224 slaughtered at constant weights.…”
mentioning
confidence: 97%
“…Even though finishing lambs at pasture is the conventional production system for lowland grasslands, some alternative feeding options may be included to finish lambs indoor or for specialist early lambing flocks which aim to market lambs in spring when prices are traditionally high, for example silage, concentrate, total mixed rations or by products [45], reaching growth rates above 300 g/d [46,47]. However, whether this alternative is economically convenient will depend upon the feed conversion efficiency and the prices of feed and meat.…”
Section: Discussionmentioning
confidence: 99%